The impacts of the COVID-19 pandemic on the opening and closing of companies and on ICMS tax collection in the state of Maranhão from 2019 to 2021 (International Seven Journal of Health Research, 2024)
The objective of this scientific research is to identify the impacts of the pandemic caused by COVID-19 on the economy of the state of Maranhão (Brazil), aiming at this purpose, aiming at the evolution of ICMS revenues and the balance between the opening and closing of companies during the peak of the disease in the state. The variables were validated after a review of the existing literature that address the origins of COVID-19, originating from the Asian continent and spread around the world until arriving in Brazil, especially in Maranhão, and the ICMS was also conceptualized from the perspective of indirect tax and on the consumption of families and companies. The study will use data/documents made available in the official media of the national state and Maranhão, with a quantitative approach, using a statistical tool "R" and exploratory and descriptive purposes. Even early to determine precisely the real impacts of the pandemic on the Economy of Maranhão, it is possible to observe signs of negative trends both for the formal continuity of companies and for the collection of ICMS in Maranhão; when compared only the months "with" and "without" the pandemic in the years 2019/2020 can already extract statistically the first the direct effects caused by the paralizations both in the collection and in the opening and closing performance of new businesses. Given the information based on the research, the intention is not to exhaust the subject, but to have a study that will serve as an initial step for future surveys and thus contribute to the scientific and academic community that can better understand what is happening with the economies and effects of this virus.